Demographic Diversity in Top Level Management and Its Implications on Firm Financial Performance: An Empirical Discussion - Marimuthu, Maran (2009)
This paper explores how demographic diversity in top level management affects firm financial performance. Top level management refers to both top management team and board of directors. Thus, the purpose of this paper is to empirically examine the effect of demographic diversity on top management team and boards of directors with regard to firm financial performance. This paper uses both financial and non-financial data from top 100 non-financial listed companies over the period 2000 to 2006, using the non-probability sampling approach. Demographic diversity comprises of ethnic and gender diversity and performance is measured by Return on Equity (ROE). A Pooled Least Square (PLS) regression method is used and hierarchical regression analyses are presented accordingly. The results indicate that demographic diversity has some significant impact on boards of directors with regard to firm financial performance. However, demographic diversity in TMTs does not create any significant impact on firm financial performance.